Uganda : : Medical and sanitary conditions - Great Britain Colonial Office; Uganda Medical Dept; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1934)
Colonial Office file relating to health conditions and the policy of the Medical Dept. in Uganda, 1934